Molecular structure and nitrite-bonded study on copper(II) complexes of N, N-dialkyl, N′-benzyl-ethylenediamine; synthesis, spectroscopic characterization, X-ray structure, steric effect and density functional theory calculations. (18th April 2015) - Golchoubian, Hamid; Khazaee, Zeynab; Rezaee, Ehsan; Moayyedi, Golasa; Farmanzadeh, Davood
Graphical abstract: An investigation on the geometric structures, spectroscopic properties and electronic structures of copper(II)-nitrito complexes as a function of steric effects utilizing a set of closely related coligands were carried out experimentally and theoretically. Depending on the steric crowding of the coligand, the coordination mode of the nitrite ligand is either symmetric or asymmetric bidentate. Abstract: Presented here is an investigation on the geometric (molecular) structures, spectroscopic properties and electronic structures of copper(II)-nitrite complexes as a function of steric effects, utilizing a set of closely related co-ligands. The prepared complexes, with the general formula [CuL R (η 2 -ONO)2 ] where L R is N, N -dialkyl, N ′-benzyl-ethylenediamine and R is methyl, ethyl or isopropyl moieties, were structurally characterized by physico-chemical and spectroscopic methods. An X-ray diffraction study on CuL Me (η 2 -ONO)2 ] and CuL Et (η 2 -ONO)2 ] reveals that the copper(II) center in both compounds is located in a distorted octahedral environment through coordination of two amine nitrogen atoms and four oxygen atoms of the nitrite ligands. Depending on the steric crowding of the co-ligand, the coordination mode is either symmetric or asymmetric bidentate, as is evident from X-ray crystallography and IR spectroscopy. The relative stability of linkage isomers of these compounds, along with a tert -butyl derivative complex, was investigated using density functional theory (DFT) calculations. The calculated results demonstrated that in all cases the bidentate η 2 -ONO isomer is more stable than the four-coordinated nitro isomer (η 1 -NO2 ). However, the differences in the relative stability decrease as the steric hindrance in the co-ligand increases. The vibrational spectra of the complexes were assigned using DFT calculations. In support with the X-ray structure, the results reveal that ν as (N–O) splits into two bands, with the separation increasing from [CuL Me (η 2 -ONO)2 ] through to [CuL tert-buty (η 2 -ONO)2 ]. That is at least partially dictated by steric factors within the molecules, imposed by the alkyl groups of the co-ligand. The UV–Vis absorption spectra are presented and analyzed with the help of time-dependent density functional theory (TD-DFT) calculations.